Daphnia magna microRNAs respond to nutritional stress and ageing but are not transgenerational. Issue 6 (7th March 2018) - Hearn, Jack; Chow, Franklin Wang‐Ngai; Barton, Harriet; Tung, Matthew; Wilson, Philip J.; Blaxter, Mark; Buck, Amy; Little, Tom J.
Abstract: Maternal effects, where the performance of offspring is determined by the condition of their mother, are widespread and may in some cases be adaptive. The crustacean Daphnia magna shows strong maternal effects: offspring size at birth and other proxies for fitness are altered when their mothers are older or when mothers have experienced dietary restriction. The mechanisms for this transgenerational transmission of maternal experience are unknown, but could include changes in epigenetic patterning. MicroRNAs (miRNAs) are regulators of gene expression that have been shown to play roles in intergenerational information transfer, and here, we test whether miRNAs are involved in D. magna maternal effects. We found that miRNAs were differentially expressed in mothers of different ages or nutritional state. We then examined miRNA expression in their eggs, their adult daughters and great granddaughters, which did not experience any treatments. The maternal (treatment) generation exhibited differential expression of miRNAs, as did their eggs, but this was reduced in adult daughters and lost by great granddaughters. Thus, miRNAs are a component of maternal provisioning, but do not appear to be the cause of transgenerational responses under these experimental conditions. MicroRNAs may act in tandem with egg provisioning (e.g., with carbohydrates or fats), and possibly other small RNAs or epigenetic modifications.